Remittances, Financial Sector Development, Efficiency, and Growth in Africa - Dolapo, Raheem Ibrahim (Indian Journal of Finance, 2015)
The study modelled the relationship between remittances and economic growth and its interaction with financial development and efficiency. Using dataset for 44 countries in Africa for the period from 1998 to 2012, the results obtained showed that remittances are positively related to growth. Remittances impact more in recipients’ economies with a less-developed financial sector. Quantity-based indicators of financial development impacted mildly on economic growth as compared to the quality-based indicators. The interaction between remittances and the quality-based indicators was more important to growth than the interaction between remittances and quantity based indicators. These results are robust to the threshold estimation. The study recommended the design of policies that would facilitate improvements in the quality-based indicators, a situation that has previously been ignored.